2018
DOI: 10.1002/jnr.24307
|View full text |Cite
|
Sign up to set email alerts
|

White matter changes associated with cognitive visual dysfunctions in children with cerebral palsy: A diffusion tensor imaging study

Abstract: Children with cerebral palsy often present with cognitive-visual dysfunctions characterized by visuo-perceptual and/or visuo-spatial deficits associated with a malfunctioning of visual-associative areas. The neurofunctional model of this condition remains poorly understood due to the lack of a clear correlation between cognitive-visual deficit and morphological brain anomalies. The aim of our study was to quantify the pattern of white matter abnormalities within the whole brain in children with cerebral palsy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
11
0
2
Order By: Relevance
“…Nonetheless, both individuals had cognitive visual problems; this was not an unexpected finding since the peritrigonal white matter is a known site of WMDI 27 . A recent dMRI study showed an association between diffusion parametric changes in the superior longitudinal fascicles and cognitive visual dysfunction in children with CP, 28 highlighting the potential of studying white matter pathways involved in higher‐order visual processing in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, both individuals had cognitive visual problems; this was not an unexpected finding since the peritrigonal white matter is a known site of WMDI 27 . A recent dMRI study showed an association between diffusion parametric changes in the superior longitudinal fascicles and cognitive visual dysfunction in children with CP, 28 highlighting the potential of studying white matter pathways involved in higher‐order visual processing in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are first shown a set of progressively complex geometric shapes (in total 27), and on each item they are asked to draw it by him/herself. (3) In the Street Completion Test 129 , 130 , participants have to recognize 11 black-and-white fragmented images that represent real objects with increasing ambiguity. (4) The Unusual Perspective test and Unusual Lighting test developed from scratch 130 , 131 contain 22 colour photographs of objects (22 images of objects photographed from unusual viewpoints and 22 images of objects presented under unusual lighting conditions) and photographs of the same objects presented in a conventional manner.…”
Section: Methodsmentioning
confidence: 99%
“…Participants have to indicate whether each item represents an animal or object that really exists. (6) In addition, two tests (described below) are aimed at assessment of semantic categorization 129 , 130 . Both the Matching by Class and the Matching by Function tests consist of 20 out of the 64 items of the original test (the Birmingham Object Recognition Battery 131 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thinning and decreased fractional anisotropy within the SLF has been shown to be a biomarker for PVD in children with cerebral palsy. [ 19 ]…”
Section: Higher Visual Processingmentioning
confidence: 99%